Accelerating water evaporation from salty droplets on polar substrate: a molecular dynamics study. Issue 15 (4th April 2023) - Huang, Yongfeng; Liang, Yingzong; Xu, Shun
Abstract : Electrostatic interactions inside a droplet suppress water evaporation. However, interactions induced by a polar substrate promote evaporation, since the interaction decreases the evaporation barrier and enlarges the contact diameter. Abstract : Evaporation of seawater containing various ions is the largest source of rainfall, affecting the global climate. In industrial areas, water evaporation finds applications in the desalination of seawater to get fresh water for arid coastal regions. Understanding how ions and substrates influence the evaporation of sessile salty droplets on a substrate is essential to modulate the evaporation rate. In the present study, we investigate the effect of ions (Mg 2+, Na +, Cl − ) on the evaporation of water molecules from sessile droplets on the solid surface using molecular dynamics simulations. The electrostatic interactions between water molecules and ions suppress water evaporation. However, the interactions between molecules and atoms in the substrates accelerate the evaporation. We increase the evaporation of salty droplets by 21.6% by placing the droplet on the polar substrate.